BUAH ZAITUN PRESPEKTIF AL-QUR'AN & SAINS (TELAAH Q.S AL-AN'AM AYAT 99 DALAM TAFSIR MAFATIHUL GHAYB) - Khusna, Niatul (Universitas Nahdlatul Ulama Surakarta, 2025)
Plants are the foundation of most terrestrial ecosystems. In thematic encyclopedias it is explained that plants are the key to life. Without them, other organisms will perish. Plants are included in the part of very valuable natural resources so that their sustainability needs to be maintained so that the diversity of plant and animal species and their ecosystems do not become extinct. In the Qur'an, Surah Al-An'am/6:99 Allah SWT emphasizes that Allah SWT created various types of plants to meet the food needs of mankind, plants can grow and revive previously dry land, plants also provide benefits for life, both as food, medicine, and natural beauty. Departing from the background above, the author wants to make a more in-depth study related to the special qualities of olives according to the perspective of the Qur'an and science (theory of the concept of olives in QS. al-An'am verse 99). With a qualitative approach, the data sources used in this study come from books, articles, journals, and writings that are relevant to the research theme. This research is expected to provide new insights, contributions, and a broader understanding of the topic being studied.